Use of PCR for prenatal and postnatal diagnosis of congenital rubella. - Bosma, T J (1995)
A reverse transcription-nested PCR assay (RT-PCR) was evaluated for diagnosis of congenitally acquired rubella in utero and during infancy. RT-PCR was compared with virus isolation for retrospective detection of rubella virus in placental and fetal tissues obtained after termination of pregnancy following primary rubella or rubella virus reinfection. Concordant results were obtained for 85% of samples; rubella virus RNA was detected by RT-PCR alone in four samples, and rubella virus was detected by isolation alone in two samples. Samples were also obtained for prenatal diagnosis of congenital infection; rubella virus RNA was detected in three of seven chorionic villus samples and one of three amniotic fluid samples by RT-PCR, while rubella virus was isolated in only one chorionic villus sample. To demonstrate that the RNA extracted from chorionic villus samples contained amplifiable RNA, a nested RT-PCR was used to detect keratin mRNA. Rubella virus was detected in placenta in two cases in which the fetus was uninfected, and there was no evidence of rubella virus in the placenta from one case in which the fetus was infected. Thus, detection of rubella virus in chorionic villus samples by RT-PCR may not always correctly predict fetal rubella virus infection. RT-PCR was successfully used for the diagnosis of congenitally acquired rubella in infancy. Rubella virus RNA was detected in cyropreserved or formalin-fixed lens aspirates obtained from infants in India with serologically confirmed congenital rubella but not in samples from controls with inherited cataract.